Two Realities in “The Master and Margarita” (An Introduction into the Sociology of Daily Life) - Joninas, Leonidas (Problemos, 1987)
The article deals with the chapters of M. Bulgakov’s “The Master and Margarita” in which the daily life of Moscow is described. Using A. Schutz’s idea of “plurality of realities”, the author of the article distinguishes besides the reality of the daily life three additional ones, namely, that of religious experience, of soul malady, and of crime. The latter is considered to be transcendental to the former. The social mechanics linking all the realities together is disclosed. Finally, some questions concerning the philosophical meaning of the novel are put forward.